2021
DOI: 10.3389/fimmu.2021.645320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia in Intestinal Tumors on Immune Cell Behavior in the Tumor Microenvironment

Abstract: BackgroundImbalanced nutritional supply and demand in the tumor microenvironment often leads to hypoxia. The subtle interaction between hypoxia and immune cell behavior plays an important role in tumor occurrence and development. However, the functional relationship between hypoxia and the tumor microenvironment remains unclear. Therefore, we aimed to investigate the effect of hypoxia on the intestinal tumor microenvironment.MethodWe extracted the names of hypoxia-related genes from the Gene Set Enrichment Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…This suggests that the imbalance in M0 macrophages and dendritic cells in the high-risk group may reduce the survival of patients. Previous articles have shown that cancer cells can cooperate with macrophages to promote proliferation, migration, invasion, angiogenesis, and metastasis, which are all consistent with our findings ( Huang et al, 2018 ; Wei et al, 2021 ; Xiao et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the imbalance in M0 macrophages and dendritic cells in the high-risk group may reduce the survival of patients. Previous articles have shown that cancer cells can cooperate with macrophages to promote proliferation, migration, invasion, angiogenesis, and metastasis, which are all consistent with our findings ( Huang et al, 2018 ; Wei et al, 2021 ; Xiao et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to hypoxia-mediated resistance to standard therapies, regulation of gene and protein expression, genetic instability, and malignant progression, hypoxia also plays a key role in anticancer immune response [ 9 ]. At present, the common treatment methods of oral cancer include surgery, radiotherapy, chemotherapy and anti-EGFR drugs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of each type of immune cell was calculated by the algorithm of CIBERSORT R script v1.03 ( 27 ). CIBERSORT is widely used to calculate the proportion of immune cell infiltration in the TME of solid tumors ( 28 31 ).…”
Section: Methodsmentioning
confidence: 99%